Effects of Intrinsic Motivation & Spirituality on Employees: Reducing Inner, Intra and Inter Stress - Sharma, Vikas; Singhal, R. K (Journal of Commerce and Trade, 2007)
There is a subtle and a silent relationship which exists throughout the ages, in one form of the other in the lifecycle of human beings, and in this article, I have endeavoured to investigate and Fathom that relationship which exists there. Personal growth, problem solving and personal leadership are connected in some important ways to spirituality. Learning, as we all know is a life long process and continues till the last breath and it is this continuous process that helps man to become what he is. One learnsmore at the unconscious level. When the experiences rises upto the conscious level, one has to have the capacity to experience what life offers, not at the outer level but at the inner level. By intrinsic motivation we mean a process of arousal and satisfaction in which the rewards come from carrying out an activity rather from a result of the activity. We speak of the reward being intrinsic to a task rather than the task being a means to an end that is rewarded or is satisfying. The term "iftrinsic" sometimes also occurs with a different connotation in reference to incentives which are consistent with personal qualities, intentions and values. Satisfaction gained from such incentives may be seen as intrinsic to the person rather than to the task.